2006
DOI: 10.1111/j.1440-1746.2005.04221.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognosis of nonalcoholic fatty liver disease: Is pharmacological therapy actually necessary?

Abstract: A treatment strategy comprising diet, exercise and management of associated metabolic conditions is associated with improvement in aminotransferases among patients with NAFLD. Further investigation is needed to examine the long-term efficacy of this approach on liver histology and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…In study other are in disagreement with my study (28,30,32,33). Kate hallsworth et al had only drug intervention (vitamin E) but Kittichachi and Shah had life style intervention and D + E same as our study.…”
Section: Discussioncontrasting
confidence: 55%
“…In study other are in disagreement with my study (28,30,32,33). Kate hallsworth et al had only drug intervention (vitamin E) but Kittichachi and Shah had life style intervention and D + E same as our study.…”
Section: Discussioncontrasting
confidence: 55%
“…It does not appear that weight loss is essential to create improvement in liver histology as other researchers have formerly reported [Cinar et al 2006;Zelber-Sagi et al 2007;Promrat et al 2009;Vilar et al 2009]. The majority of our study population did not experience significant weight loss and several study participants actually gained weight with improvement in liver histology.…”
Section: Discussionmentioning
confidence: 48%
“…Treatments including drug therapy, bariatric surgery, and lifestyle modification, have all demonstrated weight loss success. Research has shown that rapid weight loss from bariatric surgery may damage the liver and medication may not provide any substantial benefit that cannot be achieved with lifestyle modification alone [Harrison and Day, 2007;Huang et al 2005;Cinar et al 2006]. Prospective studies evaluating changes in liver histology following successful weight loss through lifestyle modification, in addition to the most beneficial type of lifestyle modification to improve liver histology in NAFLD/NASH, are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies suggest that NAFLD improves after weight loss. Improvements in liver biochemistry and ultrasonographic appearances have been found with modest weight reduction, but few studies have evaluated the effects of weight reduction on hepatic histology 45,54,55 …”
Section: Lifestyle Modificationmentioning
confidence: 99%